1988
DOI: 10.1039/dt9880000557
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the reaction of [Mo(η-C6H6)(Me2PCH2CH2PMe2)(η-C2H4)H]+with PMe3giving [Mo(η-C6H5Et)(dmpe)(PMe3)H]+: metal-to-ring migration of an ethyl group

Abstract: Non-S.I. units employed: eV z 1.60 x J, atm = 101 325 Pa. Results and DiscussionSynthesis of New Compounds.-The study of the mechanism of reaction ( 2 ) necessitated the synthesis of several new compounds which will be described before the mechanistic studies. The analytical, mass, n.m.r., and i.r. spectroscopic data which characterise the new compounds are given in Table 1. These data are not discussed further except where the interpretation is not straightforward. The structures proposed for the new compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thus, the base-induced migration of organic (9) 2.042(8), 2.040(10); 2.041 (9) 2.030 (9), 2.019(5); 2.024 (9) 2.04 (1) (3) 2.047 (6) 2.007 (3) 2.028 (4) 2.059(3) Ru-C (1) 1.979 (4) 1.988 (3) 1.963 (10) 1.987 (6) 2.046 (3) 1.915 (4) 1.973 (3) 2.7324 (4) [I] C(1)-C(2) 1.225 (5) (2) fragments has been reported for systems such as Co(PMe 3 ) 2 Cp complexes bearing acyl groups [22] and transfer of SiMe 3 groups from iron [23] while similar reactions leading to amination of the Cp ring are known [24]. Extensive studies of arene-molybdenum complexes [25] and acyl-iron derivatives [26] have concluded that nucleophilic attack at the metal centre results in migration of the carbon ligand to the p-ring, followed by loss of H. A closely related example is the reaction between Ru-(C"CPh)(PPh 3 ) 2 Cp and C 2 (CO 2 Me) 2 to give RuCl-(PPh 3 ) 2 (g-C 5 H 4 C"CCO 2 Me) during which, however, some process akin to alkyne metathesis has also occurred [27], while more recently, Lo Sterzo [28] has found either palladium-or LiBu-induced migrations in several cyclopentadienyl-metal carbonyl alkyls. In the present transformation of 8 into 9, attack by iodide at the ruthenium centre prompts the migration of the alkynyl substituent to the C 5 ring.…”
Section: Molecular Structuresmentioning
confidence: 98%
“…Thus, the base-induced migration of organic (9) 2.042(8), 2.040(10); 2.041 (9) 2.030 (9), 2.019(5); 2.024 (9) 2.04 (1) (3) 2.047 (6) 2.007 (3) 2.028 (4) 2.059(3) Ru-C (1) 1.979 (4) 1.988 (3) 1.963 (10) 1.987 (6) 2.046 (3) 1.915 (4) 1.973 (3) 2.7324 (4) [I] C(1)-C(2) 1.225 (5) (2) fragments has been reported for systems such as Co(PMe 3 ) 2 Cp complexes bearing acyl groups [22] and transfer of SiMe 3 groups from iron [23] while similar reactions leading to amination of the Cp ring are known [24]. Extensive studies of arene-molybdenum complexes [25] and acyl-iron derivatives [26] have concluded that nucleophilic attack at the metal centre results in migration of the carbon ligand to the p-ring, followed by loss of H. A closely related example is the reaction between Ru-(C"CPh)(PPh 3 ) 2 Cp and C 2 (CO 2 Me) 2 to give RuCl-(PPh 3 ) 2 (g-C 5 H 4 C"CCO 2 Me) during which, however, some process akin to alkyne metathesis has also occurred [27], while more recently, Lo Sterzo [28] has found either palladium-or LiBu-induced migrations in several cyclopentadienyl-metal carbonyl alkyls. In the present transformation of 8 into 9, attack by iodide at the ruthenium centre prompts the migration of the alkynyl substituent to the C 5 ring.…”
Section: Molecular Structuresmentioning
confidence: 98%
“…Unlike with alkenes, direct observation of arene insertion into metal-hydride bonds is rare with examples reported for cobalt, iron, and niobium . Little is known, for example, about the site selectivity for insertion of a substituted arene into a metal-hydride bond, i.e., if a C­(sp 2 )–C­(sp 2 )– H or a C­(sp 2 )–C­(sp 2 )– R bond of a monosubstituted arene C 6 H 5 R would insert preferentially.…”
Section: Introductionmentioning
confidence: 99%